Innovation of the Education of College Students' Outlook on Life Following Positive Psychology Under the Theory of Educational Psychology - Long, Xiao; Chen, Peiyao; Liu, Qingquan; Zhang, Fengrui; Lu, Chao (Frontiers in Psychology, 2022)
The study expects to find a better way to improve the teaching quality of the education of college students’ outlook on life based on the theory of educational psychology. First, the relevant theories of positive psychology are introduced and expounded, and the importance of the education of college students’ outlook on life is analyzed. Second, the current situations of college students’ outlook on life and the education of their outlook on life are investigated through a questionnaire survey, and the problems presented in the questionnaire are analyzed. Then, the correlation between positive psychology and the education of college students’ outlook on life is explored, and their mutual connection is analyzed. The results show that 77.4% of the college students have periodical aims and work hard for them; 80.8% of the students think that the realization of life goals rely on hard work, accounting for the largest proportion; When they encounter setbacks, more than 80% of the students choose to work hard to overcome them; 69.2% students think that their outlook on life comes from self-learning and exploration. According to college students' outlook on life in China and foreign countries, there are many problems in the education of college students’ outlook on life, and the teaching quality of the education of college students’ outlook on life is backward. The combination of positive psychology and college students' education of college students’ outlook on life under the theory of educational psychology provides new ideas and ways for college students' education of college students’ outlook on life. The conclusion of this study promotes the innovation of the education of college students’ outlook on life.